Dinamika Hukum Perlindungan Konsumen dalam Labirin Sengketa Properti - Evelyn; Ariawan Gunadi (Jurnal Hukum Lex Generalis, 2024)
The property sector in Indonesia plays a crucial role in the financial stability of families and individuals. However, property transactions are often marked by disputes arising from unclear agreements, delays in handover, and discrepancies in building quality. A lack of sufficient knowledge and limited access to legal resources make consumers vulnerable to fraud and unfair practices. This journal explores the role of consumer protection law in effectively resolving property disputes and highlights challenges in the implementation of consumer protection regulations in property disputes. Recommendations include legislative reform, strengthening the capacity of regulatory bodies, and enhancing educational programs. This study aims to strengthen consumer protection in the property sector.